First experimental-based characterization of oxygen ion beam depth dose distributions at the Heidelberg Ion-Beam Therapy Center - Kurz, Christopher; Mairani, Andrea; Parodi, Katia (Physics in medicine and biology, 2012)
Over the last decades, the application of proton and heavy-ion beams to external beam radiotherapy has rapidly increased. Due to the favourable lateral and depth dose profile, the superposition of narrow ion pencil beams may enable a highly conformal dose delivery to the tumour, with better sparing of the surrounding healthy tissue in comparison to conventional radiation therapy with photons. To fully exploit the promised clinical advantages of ion beams, an accurate planning of the patient treatments is required. The clinical treatment planning system (TPS) at the Heidelberg Ion-Beam Therapy Center (HIT) is based on a fast performing analytical algorithm for dose calculation, relying, among others, on laterally integrated depth dose distributions (DDDs) simulated with the FLUKA Monte Carlo (MC) code. Important input parameters of these simulations need to be derived from a comparison of the simulated DDDs with measurements. In this work, the first measurements of 16 O ion DDDs at HIT are presented with a focus on the determined Bragg peak positions and the understanding of factors influencing the shape of the distributions. The measurements are compared to different simulation approaches aiming to reproduce the acquired data at best. A simplified geometrical model is first used to optimize important input parameters, not known a priori , in the simulations. This method is then compared to a more realistic, but also more time-consuming simulation approach better accounting for the experimental set-up and the measuring process. The results of this work contributed to a pre-clinical oxygen ion beam database, which is currently used by a research TPS for corresponding radio-biological cell experiments. A future extension to a clinical database used by the clinical TPS at HIT is foreseen. As a side effect, the performed investigations showed that the typical water equivalent calibration approach of experimental data acquired with water column systems leads to slight deviations between the experimentally determined and the real Bragg peak positions. For improved accuracy, the energy dependence of the stopping power, and herewith the water equivalent thickness, of the material downstream of the water tank should be considered in the analysis of measured data.
Gesehen am 02.11.2018